THE EFFECT OF ZAKAT, INFAQ, AND SADAQAH (ZIS), TAXES, AND SUBSIDIES ON REDUCING POVERTY LEVELS IN INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to see the effect of zakat, infaq, and sadaqah (ZIS), taxes, and subsidies on reducing poverty levels in Indonesia. The data used in this study are secondary data in the form of panel data obtained from the annual report of the Central Statistics Agency (BPS), the financial statements of the Directorate General of Fiscal Balance (DJPK), and the National Amil Zakat Agency (BAZNAS), from 2018 to 2022, consisting of 34 provinces in Indonesia. The dependent variable in this study is the poverty rate, while the independent variables are ZIS (zakat, infaq, sadaqah), taxes, and subsidies. To determine the effect of zakat, infaq, and sadaqah (ZIS), taxes, and subsidies on poverty reduction in Indonesia using panel data regression analysis method. The results showed that one of the three independent variables studied had a partial effect on reducing poverty in Indonesia, namely the variable zakat, infaq, and sadaqah (ZIS), which had a positive and significant effect. Meanwhile, the tax and subsidy variables have a negative but insignificant effect in Indonesia. Simultaneously, zakat, infaq, and sadaqah (ZIS), taxes, and subsidies affect poverty reduction in Indonesia.
Keywords: Poverty; ZIS; Taxes; Subsidies